2016
DOI: 10.1016/j.jpedsurg.2016.02.093
|View full text |Cite
|
Sign up to set email alerts
|

3D printing to simulate laparoscopic choledochal surgery

Abstract: Aims of the Study:Laparoscopic simulation has transformed skills acquisition for many procedures. However, realistic non-biological simulators for complex reconstructive surgery are rare. Life-like tactile feedback is particularly difficult to reproduce. Technological innovations may contribute novel solutions to these shortages. We describe a hybrid model, harnessing 3D technology to simulate laparoscopic choledochal surgery for the first time. Methods:Digital hepatic anatomy images and standard laparoscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…In addition to using 3D printed anatomic models to simply gain a more accurate perception of the patient's anatomy, these models have also been used to perform mock surgeries pre-operatively with patient-specific anatomy. This can be highly valuable in the planning of surgery in a patient with highly complex or rare surgical pathology (64).…”
Section: Anatomic Models: Pre-surgical Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to using 3D printed anatomic models to simply gain a more accurate perception of the patient's anatomy, these models have also been used to perform mock surgeries pre-operatively with patient-specific anatomy. This can be highly valuable in the planning of surgery in a patient with highly complex or rare surgical pathology (64).…”
Section: Anatomic Models: Pre-surgical Simulationmentioning
confidence: 99%
“…In pediatric surgery, published examples of pre-surgical patient specific simulations include laparoscopic choledocal cyst excision (64) and thoracoscopic infant lobectomy (71). These authors found pre-surgical simulation to be a valuable tool.…”
Section: Anatomic Models: Pre-surgical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen of the 32 studies refer to the utilization of 3D printed organs, based on the patients’ CT and MRI imaging data, to establish a better understanding of the lesions and the surrounding structures pre-operatively[16,20-33]. Ten studies refer to the use of 3D printed objects for educational uses[28,32,34-41], while seven studies describe and evaluate the technical properties of 3D printed models[34-36,42-45]. Other uses of 3D printing techniques account for six of the included studies[32,46-50].…”
Section: Current Status and Challenges Of 3d Printing In Hepatic Surgerymentioning
confidence: 99%
“…3D-printed liver models have also been shown to be effective tools in teaching the anatomy of hepatic segments to medical students [8]. The fastest growing and most innovative use for liver phantoms is procedure simulations; thus far, phantom simulations have been reported for laparoscopic choledochal cyst excision surgery and hepatoblastoma resection in pediatric patients and endoscopic ultrasound-guided biliary drainage [9][10][11]. Despite the fact that 3D-printed models for procedure simulation are ideally suited for interventional radiology, there are currently no reports of a hepatobiliary phantom having been manufactured for this purpose or for specific use in this field.…”
Section: Introductionmentioning
confidence: 99%